Man as symbol maker creating new meanings - Contemporary Arts Media; Center for Humanities ([New York] : Center for Humanities : Contemporary Arts Media [distributor], 1990)
This program examines human communication in all its aspects: as an expression of culture; in literature and art; in personal relationship. It provides a penetrating analysis of how men and women have, since earliest times, used symbols to express basic ideas about themselves and the world in which they live. Examines the impact of symbols and images used in art and literature to describe people's most profound thoughts and feelings.
Title from container.
DVD format.
Keywords: Semiotics; Signs and symbols -- Social aspects; Symbolism in art; Symbolism in literature